Performance of LEED energy credit requirements in European countries - Gurgun, Asli Pelin; Polat, Gul; Damci, Atilla; Bayhan, Hasan Gokberk (ELSEVIER SCIENCE BV, 2016)
Construction industry influences the environment a great deal by using different resources. Efficient use of resources is important for sustainability considerations. Heavy consumption of energy is one of the reasons causing adverse impacts on the built environment. The interest in sustainable construction is growing worldwide. Green building systems are used to certify the projects as green buildings in different countries. All these systems have similar approaches to build sustainably and they all highlight requirements related to energy consumption with a significant emphasis. One of the most recognized green building certification systems, LEED addresses energy optimization, green power and on-site renewable energy in much detail. The maximum credit points can be achieved from energy and atmosphere category in LEED. However, the use of LEED in countries other than the U.S. can be difficult as local conditions and practices are influential in earning credentials. This study aims to review the practices of energy and atmosphere category of LEED v3 2009 New Construction in European countries. Analysis of practices in selected countries is made based on credit performances, which can display variations depending on local conditions. It is expected that practitioners in these countries will benefit from the credit patterns, providing improved insights about on-site real applications. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: LEED; energy and atmosphere; Europe; sustainable construction; credit; Construction & Building Technology